The Role of Innovative Technologies in Teaching Phonetic Exercises in Primary School - Muxammadjonova Sayyorakhon (Zien Journals, 2022)
The article discusses the ideas on how to form literary pronunciation in students by teaching phonetics, increase spelling literacy, vocabulary, improve the development of content, methods and tools for the development of independent thinking skills.
Keywords: globalization; phonetics; pronunciation; stress